My Child Has a Mental Illness: Developing Parental Advocacy Skills - Tracy DeCubellis; Victor William Harris; Martie Gillen (EDIS)
If your child is diagnosed with a mental illness, you will face major changes in your life. Being proactive about your child’s care and advocating for him or her will help you and your child handle the illness successfully. This 5-page fact sheet was written by Tracy DeCubellis, Victor W. Harris, and Martie Gillen, and published by the UF Department of Family Youth and Community Sciences, April 2013.